(untitled) (Journal of Civil Engineering Researchers, 2024)
Recycled glass waste is one of the most attractive waste materials that can be used to create a concrete mix.Therefore, researchers focus on the production of concrete using recycled glass as an abrasive or as a pozzolanic material, but the use of recycled glass in the form of coarser particles to replace sand in concrete increases the alkali-silica reaction and this causes Unfavorable performance in the mechanical properties of concrete.To prevent this, microsilica is used to improve the strength and mechanical properties of concrete.In this research, after building the control mixing design, recycled glass was replaced with sand and silica foam as microsilica in four designs with a fixed ratio of 5% by weight of cement.The compressive strength test was performed at the ages of 7 and 28 days, and three samples were taken in each test, and a total of 24 cubic samples were tested.Tensile test, like compressive strength test, were tested at the ages of 7 and 28 days, which included two cylindrical samples in each test, and a total of 16 cylindrical samples were tested.The presence of silica foam in concrete causes adhesion and reduction of slump fluidity, and the highest slump fluidity was observed at 5% ratio.The result of testing the compressive strength and tensile strength of the concrete containing glass shards and silica foam had decreased in quality compared to the control mixing plan, which shows the unfavorable performance of coarse glass particles in the concrete structure.